The impact of withdrawal of international non-governmental organisations from public health facilities: A case study of Tsholotsho district, Matabeleland North Province, Zimbabwe - Hamisi, Rashid (Department of Public Health and Family Medicine, 2022)
International non-governmental organisations (INGOs) play a critical role in improving the capacity of health systems to deliver services in sub-Saharan Africa (SSA), especially in fragile and conflict affected states (FCAS). Nonetheless, the sustainability of public private engagement (PPE) initiatives between health systems and INGOs is threatened by various factors including, decline in developmental and humanitarian assistance and a shift in policies and priorities. Consequently, many INGOs are exiting PPE initiatives. There is a lack of evidence about the process of withdrawal of INGOs from low- and middle-income countries and FCAS settings, in particular, how the nature of the withdrawal (beyond the basic loss of funds) affects the functioning of the health system, especially at lower levels of primary care. This mini dissertation presents a research protocol (Section A), and a journal formatted manuscript (Section B) for a case study of the impact of withdrawal of INGOs from public health facilities in Tsholotsho district, Matabeleland North Province, Zimbabwe. This study describes the process of withdrawal by three INGOs from PPE initiatives with Tsholotsho District Hospital (TDH). Understanding this process better and learning how public health facilities cope with the withdrawal of partner support, provides lessons on how to efficiently sustain the gains from PPE initiatives. In these three cases, PPEs were ended because of an ending of funds. Despite the existence of exit and sustainability plans, in all cases, the withdrawal process was fraught and difficult to navigate. There was a discrepancy between plans and what transpired during and after funding-withdrawal. The common issues that affected exit implementation included abruptness of the withdrawal by INGOs; lack of resources to sustain the intervention after withdrawal of funding; and design, depth and scope of intervention. In addition, lack of clear regulatory mechanisms that shape PPE initiatives and govern the withdrawal of partners from public facilities also affected the process. Due to these factors, the interventions either stopped or continued at a drastically reduced scale. Withdrawal of partners, especially in FCAS, has dire implications for the health system, and need to be managed with much greater attention given to (unintended) consequences to the health system and its resilience. Health system assessments and analytics should be performed by expert independent parties prior to the ending of PPEs, which would enable context-specific withdrawal plans that might aid in mitigating future difficulties.